A brief history of justice - Johnston, David 1951- (Brief histories of philosophy., 2011)
"A Brief History of Justice traces the development of the idea of justice from the ancient world until the present day, with special attention to the emergence of the modern idea of social justice. An accessible introduction to the history of ideas about justice Shows how complex ideas are anchored in ordinary intuitions about justice Traces the emergence of the idea of social justice Identifies connections as well as differences between distributive and corrective justice Offers accessible, concise introductions to the thought of several leading figures and schools of thought in the history of philosophy "-- Provided by publisher.